A FOOTNOTE TO EINSTEIN 1907 - Rossler, Otto E. (European Scientific Journal, ESJ, 2014)
An add-on to Einsteinâ€™s equivalence principle of 1907, specifically to its third point, is offered. The three points read: (1) gravitational redshift, (2) gravitational light-ray bending, and (3) local reduction of the speed of light c. The third point can be replaced by a more general effect that explains it: (3â€™) gravitational light-ray tilting. The consequence is â€œglobal constancy of the speed of light c.â€ This retrieved implication of the equivalence principle is bound to carry over to general relativity. A new â€œanalogicalâ€ subfield of digital numerical simulations is called for.